Effect of Compressive Strength of Red Brick with the Addition of Carrageenan - Nofriadi; Dary, Rhini Wulan; Oktaviani, Tetra; Putri, Wirdatun Nafiah; Putra, Heriansyah (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Red brick is one of the building materials used to make building walls. Red bricks are made from clay and can be mixed using additives. The use of clay has the most composition in the red brick mixture. Adding addictive materials is an effort that many researchers have made to improve the quality of red bricks. In this study, researchers were interested in using carrageenan as a mixture of red bricks. The research was carried out experimentally in the laboratory by making brick samples measuring 5 cm x 5 cm x 5 cm with various mixtures of BMC (control), BMK5 with the addition of 5% carrageenan, BMK10 with the addition of 10% carrageenan, and BMK15 with the addition of 15% carrageenan with drying temperature 50°C, 100°C, and 150°C for 24 hours.Research data was obtained through an experimental process of testing the compressive strength of red bricks using a compression test equipment. The data obtained was processed to obtain the compressive strength value of the red brick. The results showed that addition of 5% of the carrageenan mixture had an effect on the compressive strength of the red brick. Addition of 5% carrageenan contributed to the increase in the compressive strength of the red brick. There was a decrease in the compressive strength of the red brick in the sample with the percentage of addition carrageenan by 10% and 15 %. The ideal drying temperature for a mixture of red bricks with carrageenan is at 50℃ for 24 hours.